A Systematic Review of the Level of Evidence in Economic Evaluations of Medical Devices: The Example of Vertebroplasty and Kyphoplasty - Martelli, Nicolas; Devaux, Capucine; van den Brink, Hélène; Pineau, Judith; Prognon, Patrice; Borget, Isabelle (PloS one, 2015)
Economic evaluations are far less frequently reported for medical devices than for drugs. In addition, little is known about the quality of existing economic evaluations, particularly for innovative devices, such as those used in vertebroplasty and kyphoplasty. To assess the level of evidence provided by the available economic evaluations for vertebroplasty and kyphoplasty. A systematic review of articles in English or French listed in the MEDLINE, PASCAL, COCHRANE and National Health Service Economic Evaluation databases, with limits on publication date (up to the date of the review, March 2014). We included only economic evaluations of vertebroplasty or kyphoplasty. Editorial and methodological articles were excluded. Data were extracted from articles by two authors working independently and using two analysis grids to measure the quality of economic evaluations. Twenty-one studies met our inclusion criteria. All were published between 2008 and 2014. Eighteen (86%) were full economic evaluations. Cost-effectiveness analysis (CEA) was the most frequent type of economic evaluation, and was present in 11 (52%) studies. Only three CEAs complied fully with the British Medical Journal checklist. The quality of the data sources used in the 21 studies was high, but the CEAs conforming to methodological guidelines did not use high-quality data sources for all components of the analysis. This systematic review shows that the level of evidence in economic evaluations of vertebroplasty and kyphoplasty is low, despite the recent publication of a large number of studies. This finding highlights the challenges to be faced to improve the quality of economic evaluations of medical devices.